Prognostic factors for survival in patients with lung metastases from gynaecological tract cancers. (3rd August 2021) - Chiappetta, Marco; Gallotta, Valerio; Pogliani, Luca; Zanfrini, Edoardo; Fagotti, Anna; Ferrandina, Gabriella; Fanfani, Francesco; Nachira, Dania; Meacci, Elisa; Congedo, Maria Teresa; Lococo, Filippo; Giudice, Maria Teresa; et al.
Abstract: : OBJECTIVES: Lung metastases from gynaecological tract cancers are rare, and prognostic factors are still undefined. The goal of this study was to analyse prognostic factors for survival in this group of patients. METHODS: Data of patients with lung metastases from gynaecological tract cancers who underwent surgical resections from 1 January 2005 to 31 May 2019 were reviewed retrospectively. All patients were treated surgically if the primitive tumour was under control and the lung was the only organ involved. Clinical and pathological data associated with metastatic patterns and previous treatment types were correlated with overall survival (OS) and disease-free survival using Kaplan–Meier curves, whereas the log-rank test was used to assess differences between subgroups. RESULTS: The analysis was conducted on 55 patients. OS was 65% at 5 years. With univariable analysis, age >45 years ( P = 0.022) and the absence of pleural infiltration ( P = 0.001) were determined to be favourable prognostic factors. The 5-year OS was 69.9% versus 53.3% in patients with pleural involvement. Multivariable analysis confirmed the absence of pleural infiltration as a favourable independent prognostic factor; the hazard ratio was 0.06; the 95% confidence interval was 0.00–0.23 ( P = 0.011). At univariable analysis, the absence of pleural infiltration was determined to be a favourable prognostic factor ( P = 0.034) for disease-free survival. The numbers and dimensions of the metastases did not influence survival in these patients. In uterine cancers of endometrial or cervical origin, the presence of pleural infiltration ( P = 0.001), lymph node involvement ( P = 0.001) and young age ( P = 0.044) were considered unfavourable prognostic factors for OS. CONCLUSIONS: Surgical treatment in technically resectable gynaecological tract metastases may represent an important option. Pleural infiltration and lymph node metastases seem to be adverse prognostic factors. Abstract : The standard treatment for recurrent gynaecological cancer is systemic chemotherapy or radiotherapy, even though new target therapies and tailored approaches are emerging [1–3].